اختلافات الشافعية والحنابلة في صفات الصلاة الفعلية: Comparative Analysis of the Prayer Movement in the Shafii and Hanbali Schools - Sirajuddin Sirajuddin; Nuraeni Novira; Awal Rifai Wahab; Dian Novita Nur (Pusat Penelitian dan Pengabdian Masyarakat (P3M), Sekolah Tinggi Ilmu Islam dan Bahasa Arab (STIBA) Makassar, 2022)
Abstract This study aims to determine the differences between the Shafii and Hanbali schools in the prayer movement and its foundations. This research is a qualitative descriptive study with a comparative study technique. The results showed that: (1) the differences between the Shafii and Hambali schools in the movement of prayer were the limit of raising the hand during takbiratul ihram, the state of the fingers when lifting, the position of the right hand on top of the left hand when holding hands, raising the hand when standing from tasyahud for the third rak'ah, the position of the hands after standing from bowing, and the law of sitting and resting before giving, how to raise the index finger when pointing, and how to hold hands when tasyahud; (2) the difference between the Shafii and Hambali schools in the prayer movement is caused by differences in taking, understanding, compromising and tarjih hadith.